Use of bosentan for digital ulcers related to systemic sclerosis: a real-life retrospective French study of 89 patients treated since specific approval. (October 2014) - Agard, C; Carpentier, PH; Mouthon, L; Clerson, P; Gressin, V; Bérezné, A; Diot, E; Jego, P; Lok, C; Sparsa, A; Chatelus, E; Van Kien, A Khau; et al.
<x xml:space="preserve">Abstract</x> Objectives: Ischaemic digital ulcers (DUs) are a common complication of systemic sclerosis (SSc). This study aimed to characterize patients with SSc and ongoing DUs treated with the endothelin receptor antagonist bosentan in clinical practice in France. Method: An observational, retrospective, longitudinal study was conducted in 10 French expert centres. Medical records from randomly selected adult SSc patients who received treatment with bosentan for DU prevention from March 2007 to December 2010 were analysed. The primary objective was to determine the profile of patients at treatment initiation. Secondary objectives were to monitor bosentan dosing, treatment schedule, and reasons for treatment termination. Results: The study included 89 patients (mean age 52 years, 69% female, 44% diffuse cutaneous SSc). At bosentan treatment initiation, the mean duration of Raynaud's phenomenon was 15 ± 12 years, and the mean time since first episode with DU was 6.5 ± 7 years. Most patients had a history of at least two episodes with DUs, separated by < 12 months (61%), and had received intravenous iloprost (63%). Previous DU complications included auto-amputation (8%), surgical amputation (6%), osteitis (6%), and gangrene (4.5%). Active smokers (25%) had a history of significantly more surgical amputation (p = 0.004) and osteitis (p = 0.004) than non-smokers. At least one active DU at bosentan initiation was detected in 82% of patients. Bosentan was used according to prescription guidelines and was well tolerated; six patients (7%) withdrew from treatment because of raised liver enzymes. Conclusions: Patients treated with bosentan for DU prevention in France have severe, refractory, ongoing ulcerative disease. Active smoking was correlated to a history of DU complications. Tolerance of bosentan was comparable to previous studies.